2002
DOI: 10.1118/1.1446098
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of computerized mass detection on mammograms: Fusion of two-view information

Abstract: Recent clinical studies have proved that computer-aided diagnosis (CAD) systems are helpful for improving lesion detection by radiologists in mammography. However, these systems would be more useful if the false-positive rate is reduced. Current CAD systems generally detect and characterize suspicious abnormal structures in individual mammographic images. Clinical experiences by radiologists indicate that screening with two mammographic views improves the detection accuracy of abnormalities in the breast. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(81 citation statements)
references
References 24 publications
1
80
0
Order By: Relevance
“…In this case, radiologists compare right and left mammograms to seek for abnormalities in both images [15,55,65].…”
Section: ) Single View Lesions Detectionmentioning
confidence: 99%
“…In this case, radiologists compare right and left mammograms to seek for abnormalities in both images [15,55,65].…”
Section: ) Single View Lesions Detectionmentioning
confidence: 99%
“…Several studies have demonstrated that the fusion of information extracted from two views, CC and MLO, allow for the reduction of false positive compared to the use of a single image Paquerault et al (2002) Gupta et al (2006.…”
Section: Fusion Of Textural Informationmentioning
confidence: 99%
“…Hadjiiski et al 16 developed an interval change analysis of masses on current and prior mammograms and found that the classification accuracy of masses can be improved significantly in comparison to single image classification. Paquerault et al 17 developed a two-view (CC and MLO views) fusion technique to reduce FPs in mass detection and obtained significant improvement by comparing to their one-view detection system. van Engeland et al 18 recently presented a two-view CAD system by using the features including the difference in the radial distance from the candidate regions to the nipple, the gray scale correlation between both regions, and the mass likelihood of the regions determined by the single view CAD scheme.…”
Section: Introductionmentioning
confidence: 99%
“…The normal fibroglandular tissue in the breast causes FPs by mimicking masses and causes false negatives (FNs) due to overlapping with lesions. In order to improve the performance of our mass detection system, we are investigating computer-vision methods by incorporating information from two-view mammograms 17 and bilateral mammograms,21 emulating radiologists' mammographic interpretation techniques. In this study, we will discuss our approach to FP reduction by analyzing the symmetry or asymmetry of density patterns between bilateral mammograms.…”
Section: Introductionmentioning
confidence: 99%